What is an Efficient Implementation of the lambda-calculus? - Frandsen, Gudmund Skovbjerg; Sturtivant, Carl (DAIMI Report Series, 1991)
We propose to measure the efficiency of any implementation of the lambda-calculus as a function of a new parameter mu, that is itself a function of any lambda-expression. Complexity is expressed here as a function of nu just as runtime is expressed as a function of the input size n in ordinary analysis of algorithms. This enables implementations to be compared for worst case efficiency. We argue that any implementation must have complexity Omega(nu), i.e. a linear lower bound. Furthermore, we show that implementations based upon Turner Combinators of Hughes Super-combinators have complexities 2Omega(nu), i.e. an exponential lower bound. It is open whether any implementation of polynomial complexity, nu^0(1), exists, although some implementations have been implicitly claimed to have this complexity.